Photoacoustic waves of a fluidic elliptic cylinder: Analytic solution and finite element method study - Zhang, Ying; Wei, Huan; Fang, Hui (Frontiers in Physics, 2022)
In this study, we focused on the photoacoustic wave production of a fluidic elliptic cylinder for modelling blood vessels, where the consideration of the elliptic cross section can be important for some diagnosis of vascular diseases. First, under the condition of optically-thin absorption, the analytic solution based on the photoacoustic Helmholtz equation in elliptic cylinder coordinates by using Mathieu functions was derived. Then, the finite element method (FEM) model was established to verify the analytic solution. In addition to photoacoustic waves and corresponding photoacoustic power spectra, both near- and far-field photoacoustic amplitude angular distributions were compared. The results revealed that the angular dependent photoacoustic power spectra are critical indicators of the ellipse shape variation. This finding can provide a considerable insight into the photoacoustic diagnosis of the blood vessel changes not only in terms of sizes but also shapes.